Paradoxical decrease in isoprostane and increase in superoxide dismutase following CPAP withdrawal in OSA. - Antoniades, C; Lee, R; Kohler, M; Stradling, J (European Respiratory Society, 2016)
We thank Monneret and Bonnefont-Rousselot for their commentary. Our controlled trial design overcomes most of their concerns of course; any failure of assay techniques would not have produced a biased result, but in fact would have decreased the chances of finding any between-group effects. In our study we observed a statistically significant decrease in urinary F2-isoprostanes following the withdrawal of CPAP treatment in patients with obstructive sleep apnoea (CPAP), in a randomised, two-week trial, where those involved in the assays were entirely blind to group allocation [1]. In addition to this unexpected result, we observed no significant change in any plasma marker of oxidative stress we measured in this population (MDA, lipid hydroperoxides,) or even the production of superoxide radicals by peripheral blood mononuclear cells. It is important to note that these were morning measurements.